PHILOLOGY AND CENSORSHIP: WHO CONTROLS LANGUAGE NORMS? (SCIENCE TIME JOURNAL, 2026)
Language has always functioned as both a medium of communication and an instrument of social power. In contemporary society, linguistic norms are increasingly shaped not only by traditional philological institutions such as academies, educational systems, and literary authorities, but also by governments, media corporations, digital platforms, and algorithmic moderation systems. This article investigates the relationship between philology and censorship through the lens of critical discourse analysis, sociolinguistics, and theories of power. The study examines how language norms are established, regulated, and contested within political, educational, and digital contexts. Drawing on the theoretical contributions of Michel Foucault, Pierre Bourdieu, Norman Fairclough, and Deborah Cameron, the paper analyzes the mechanisms through which linguistic authority operates. The methodology combines qualitative discourse analysis with comparative examination of political, academic, and online communication. The findings demonstrate that censorship in modern societies rarely appears as direct prohibition alone; rather, it functions subtly through institutionalized norms, inclusive language policies, media framing, and algorithmic filtering.